Bubble dynamic behaviour of air–water two-phase flow mixing in hydraulic structures. Issue 5 (4th April 2021) - Senthilkumar, G.; Lakshmi Sankar, S.
ABSTRACT: The non-uniform flow distribution of cooling fluid in many industrial applications including chemical plants and power plants is the main cause for many heat transfer problems. This present research describes the method for achieving the uniform flow in open channel flow passages with the aid of different stream equaliser plates. The stream equaliser plate length and its porosity are varied as process parameters. The air bubble mixing nature in water is also analysed for flow uniformity.